Diabetic retinopathy predicts cardiovascular disease independently of subclinical atherosclerosis in individuals with type 2 diabetes: A prospective cohort study - Castelblanco, Esmeralda; Granado-Casas, Minerva; Hernández, Marta; Pinyol, Montserrat; Correig, Eudald; Julve, Josep; Rojo-López, Marina Idalia; Alonso, Núria; Avogaro, Angelo; Ortega, Emilio; Mauricio, Didac (Frontiers in Cardiovascular Medicine, 2022)
Background: Diabetic retinopathy (DR) and preclinical atherosclerosis are associated with higher cardiovascular risk. However, no studies have investigated the predictive role of DR and preclinical atherosclerosis jointly on cardiovascular events in subjects with type 2 diabetes (T2D). We aimed to assess the contribution of DR and subclinical atherosclerosis on the risk of major adverse cardiovascular events (MACE) in subjects with T2D without previous cardiovascular disease. Methods: We included two prospective cohorts of subjects with T2D from the same geographical area. Assessment of subclinical atherosclerosis was performed by carotid ultrasound. An ophthalmologist classified DR according to standard criteria. MACE was defined as any of the following: ischemic heart disease, stroke, heart failure, peripheral artery disease, revascularization procedures, and cardiovascular mortality. Bivariable and multivariable predictive models were performed. Results: From a total of 374 subjects with T2D 44 developed MACE during the 7.1 years of follow-up. Diabetes duration, total cholesterol, and glycated hemoglobin (HbA1c) at baseline were higher in subjects who developed MACE (p<0.001, p=0.026, and p=0.040, respectively). Compared with subjects without events, those developing MACE had higher prevalence of retinopathy (65.9% vs. 38.8%, p=0.001; respectively) and more than mild retinopathy (43.2% vs. 31.8%, p=0.002; respectively). Furthermore, all-cause mortality was higher in subjects with MACE than those without events (13.6% vs. 3.3%, p=0.009; respectively). The multivariable analyses showed that HbA1c and the presence of DR at baseline were predictive of MACE (p=0.045 and p=0.023, respectively). However, the burden of subclinical atherosclerosis was not (p=0.783 and p=0.071, respectively). Conclusions: DR is a strong predictor of cardiovascular events in T2D individuals at primary CVD prevention, even after accounting for the presence of preclinical carotid atherosclerosis. These results may help to individualize cardiovascular disease prevention strategies in T2D.